Traces of Arabian in Kumzari - van der Wal Anonby, Christina (Proceedings of the Seminar for Arabian Studies, 2014)
Kumzari is an endangered language spoken in the remote coastal villages of northern Oman. Described as the only Persian language indigenous to the Arabian Peninsula, Kumzari is related to both language families but intelligible to neither. Rather, it is a mixed language: its lexicon, phonology, and morpho-syntax are fundamentally rooted in both Arabian and Persian. Kumzari's sound-system and grammatical retentions and innovations shared with northern Omani Arabic dialects and Modern South Arabian languages attest to potential historical links. Among these, lexically pervasive emphatic consonants, Semitic roots in core vocabulary, and prolific verb derivations are immediately conspicuous as Arabian traits. More subtle features that Kumzari holds in common with Modern South Arabian languages and local Arabic varieties are the participle-like functions of Semitic-root verbs, the relative morpheme, syntax distinguishing noun/pronoun objects, and multiply marked negation. Beyond the language itself, Kumzari's historical context and geographical setting give credence to past connections and migrations across the Peninsula. Ancestors of the Kumzari people are traced to the Azd tribe, who migrated from Yemen in the third to fifth centuries AD and earlier, an era during which Oman was ruled and colonized by Sasanians. Invasions of north-central Arabians in the seventh century caused many to flee to Oman's northern mountains. Resemblances among the languages of the refugees may be a vestige of a time before the wars.